2015
DOI: 10.1109/tdei.2014.004573
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of influence of DC and AC electric fields on bridging in contaminated transformer oil

Abstract: Analysis of real operating condition revealed that HVDC transformers experience combined effect of DC biased AC electric field. The dynamics of pressboard particle in contaminated transformer oil under the influence of DC, AC and DC biased AC electric field has been investigated in this paper. Different levels of particle concentrations are tested at different applied voltages. Optical images of the particles accumulation together with conduction current have been recorded during the experiments. A complete br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…The twoparameter Weibull distribution is shown in Eq. (1), where F(u) is the probability of breakdown, α is the scale parameter and β is the shape parameter and u is breakdown [4][5][6][7] show that the breakdown voltage data of contaminated oil are distributed in both sides of the Weibull probability straight line, which indicates that the breakdown voltage data of contaminated oil almost satisfy the Weibull distribution.…”
Section: Weibull Distribution Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The twoparameter Weibull distribution is shown in Eq. (1), where F(u) is the probability of breakdown, α is the scale parameter and β is the shape parameter and u is breakdown [4][5][6][7] show that the breakdown voltage data of contaminated oil are distributed in both sides of the Weibull probability straight line, which indicates that the breakdown voltage data of contaminated oil almost satisfy the Weibull distribution.…”
Section: Weibull Distribution Analysismentioning
confidence: 99%
“…The particles in transformer insulating oil will move to the high electric field region and form impurity bridges due to the electric field force, which will reduce the breakdown strength of the insulating oil [3]. The motion of particles at combined AC and DC voltage is different from that at AC voltage, which will lead to different breakdown characteristics of contaminated insulating oil [4]. Investigation into the breakdown characteristics of transformer insulating oil contaminated with solid particles at combined AC and DC voltage is conductive to the understanding of breakdown mechanism of insulating oil used in converter transformer in presence of particle contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, when the HVDC reaches its saturated level, the current will flow through the cellulose particles between the electrodes, leading to breakdown. Several researchers have also observed this phenomenon [12], [22], [23].…”
Section: Stage Fivementioning
confidence: 71%
“…It is believed that this phenomenon occurs due to the distribution of the electric field generated between the electrodes and cellulose particles attached on the electrode surface. In addition, it has been reported that the cellulose bridge ) to flow between the electrodes [12].…”
Section: Stage Threementioning
confidence: 99%
“…Dodecylbenzene was chosen as as a model oil system whose viscosity does not change after aging [10]. Furthermore, the effect of precipitate formation on the high field performance of such oils was studied in view of particulate "bridging", which can prove troublesome in paper/oil insulation systems [7,14].…”
Section: Introductionmentioning
confidence: 99%